Biological activity of manganese(i) tricarbonyl complexes on multidrug-resistant Gram-negative bacteria: From functional studies to in vivo activity in Galleria mellonella. Issue 12 (2nd October 2019) - Güntzel, Paul; Nagel, Christoph; Weigelt, Jeanette; Betts, Jono W.; Pattrick, Calum A.; Southam, Hannah M.; La Ragione, Roberto M.; Poole, Robert K.; Schatzschneider, Ulrich
Abstract : Antibacterial activity of four Mn(CO)3 complexes on multidrug-resistant clinical isolates of A. baumannii and P. aeruginosa correlated with lipophilicity and increase in ATP release. Absence of host toxicity in G. mellonella was combined with effective bacterial clearance. Abstract : Three new manganese(i ) tricarbonyl complexes [Mn(bpqa-κ 3 N )(CO)3 ]Br, [Mn(bqpa-κ 3 N )(CO)3 ]Br, and [Mn(CO)3 (tqa-κ 3 N )]Br as well as the previously described compound [Mn(CO)3 (tpa-κ 3 N )]Br with bpqa = bis(2-pyridinylmethyl)(2-quinolinylmethyl)amine, bqpa = bis(2-quinolinylmethyl)(2-pyridinylmethyl)amine, tqa = tris(2-quinolinylmethyl)amine, and tpa = tris(2-pyridinylmethyl)amine were examined for their antibacterial activities on 14 different multidrug-resistant clinical isolates of Acinetobacter baumannii and Pseudomonas aeruginosa, in recognition of the current antimicrobial resistance (AMR) concerns with these pathogens. Minimal inhibitory concentrations (MIC) of the most potent tqa compound were in the mid-micromolar range and generally lower than that of the free ligand. Activity against both bacterial species increased with the number of quinolinylmethyl groups and lipophilicity in the order of tpa < bpqa < bqpa ≈ tqa, consistent with measured increases in release of ATP, a uniquely cytoplasmic biomolecule and induced permeability to exogenous fluorescent intercalating compounds. [Mn(CO)3 (tqa-κ 3 N )]Br was also evaluated in the Galleria mellonella model of infection, and displayed a lack of host toxicity combined with effective bacterial clearance.